2009
DOI: 10.1111/j.1398-9995.2008.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional endoscopic sinus surgery improved asthma symptoms as well as PEFR and olfaction in patients with nasal polyposis

Abstract: Functional endoscopic sinus surgery improved nasal and asthma symptoms in patients with nasal polyposis. Functional endoscopic sinus surgery could be considered early in the natural course of nasal polyposis with concomitant asthma, as well as a second-line treatment in nasal polyposis patients with a reduced sense of smell. The potential benefits of FPND 400 microg b.i.d. were probably overshadowed by FESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 24 publications
5
106
1
1
Order By: Relevance
“…The study authors were contacted via e-mail for raw data in cases of missing data. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The analyses were based on intention to treat. For missing standard deviations, either 95% CIs, 23,31,32 standard error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study authors were contacted via e-mail for raw data in cases of missing data. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The analyses were based on intention to treat. For missing standard deviations, either 95% CIs, 23,31,32 standard error.…”
Section: Discussionmentioning
confidence: 99%
“…For missing standard deviations, either 95% CIs, 23,31,32 standard error. 19,21,[33][34][35][36][37] p value, 26 range, 20 or interquartile ranges 18,20 was used for estimation to impute standard deviations. For missing means, medians were converted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…319,861,862 Using objective and subjective sinonasal and asthma outcome measures, studies have demonstrated significant clinical improvement following ESS. 320,861,[863][864][865][866] In patients with asthma and NPs, ESS was shown to improve asthma severity scores, reduce the need of inhaled corticosteroids and reduce the frequency of asthma-related emergency room visits. 863 Ehnhage et al 864 showed in a prospective randomized trial that patients with CRSwNP had a significant improvement in nasal and lower airway symptoms after ESS.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…24 One cohort study (n ϭ 32) 18 reported normal ACTH levels measured before and 1 hour after removal of corticosteroid-soaked packing gauze. 18 The reported adverse events from the included studies were blood-stained mucus, [22][23][24][25] mild epistaxis, 15,17,19 and nasal dryness. 22,23,26 …”
Section: Standard-dose Versus High-dose Incsmentioning
confidence: 99%